Dinâmica dissipativa em sistemas quânticos fortemente interagentes - Diniz, Emanuel Cardozo (2019)
In this thesis we investigate the dissipative dynamics in strongly interacting quantum systems. The dissipative dynamics that we investigate has relevance in the generation of non-classic states of light, such as the squeezed states, besides being useful in the description of phenomena give by dipole induced transparency (DIT) that are analogous to the behavior that occurs in the electromagnetic induced transparency (EIT). We show that the dissipative dynamics given by the microscopic master equation, plays a crucial role to understand correct stationary and temporal dynamics in strongly interacting systems described by spin chains. This thesis is organized in six chapters. In the second chapter, we introduce, the dissipative formalisms necessary to describe the dissipative dynamics that will be used in the following sections of this thesis. In the chapter 3, we report briefly the basic radiation-matter interaction model, i.e., the Rabi model, and its implementation in the context of circuit quantum electrodynamics (circuit QED). In the chapter 4, we provide the basic concepts of two mode squeezed states (TMSS). Next, we describe the results obtained to implement a protocol that aims to generate the two mode squeezed states in the context of circuit QED, besides discussing all the realistic dissipative mechanisms and their effects on the generation of the TMSS. In the chapter 5, we briefly discuss the phenomenon of electromagnetically induced transparency (EIT) that will be essential to understand the result of transparency induced by dipole-dipole coupling (DIT). We also introduce an approach on the effects of periodic boundary conditions on the DIT phenomenon. Finally, in the chapter 6, we discuss the dissipative dynamics in strongly interacting spin chains and clarify the correct dissipative formalism to investigate the dynamics in these systems.